PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD NEGERI 066050 MEDAN DENAI TAHUN PEMBELAJARAN 2025/2026 - Liskawaty Manullang; Ester Julinda Simarmata; Paska Sriulina Tarigan; Joen Parningotan Purba; Rizki Bastanta B. Manalu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model on the learning outcomes of fifth-grade students of SD Negeri 066050 Medan Denai in the 2025/2026 academic year. This study is motivated by the low student learning outcomes caused by the use of learning models that do not involve students' activeness and critical thinking skills in the learning process. This study uses an experimental method with a One Group Pretest-Posttest Design. The sample in this study amounted to 30 students. Data collection techniques used learning outcome tests and questionnaires. Data analysis was carried out through normality tests and hypothesis tests using the Wilcoxon Signed-Rank Test. The results showed that the average pretest score was 43.86 and the average posttest score was 81.87, resulting in an increase of 38.01. The results of the normality test indicate that the data are normally distributed. Furthermore, the results of the hypothesis test used the Wilcoxon Signed-Rank Test. The test results showed a significance value of 0.000 (p <0.05). This indicates a significant difference between the pretest and posttest scores. Therefore, Ho is rejected and Ha is accepted, indicating that the Problem-Based Learning model has an effect on the science learning outcomes of fifth-grade elementary school students at SD Negeri 066050 Medan Denai in the 2025/2026 academic year.